Community Mobilizations Around Housing and Local Environment: Insights into the Case of Vilnius - Aidukaitė, Jolanta (Sociologija. Mintis ir veiksmas, 2013)
This paper reviews activities of community organizations in the post-Soviet city of Vilnius. The particular attention is paid to the reasons for mobilization of the local communities; the leadership and motivation; the reasons for non-participation; and the communication with the local authorities. The findings of this paper show that mobilizations are not taking place on the massive scale. However, they are being institutionalized and have achieved noteworthy results. Communities mobilize against illegal or unwanted constructions close to their vicinity or to defend green zones in the city. The successful movement is centered around a charismatic leader who devotes his/her time and non-material and material resources to attain results. The explanations for non-participation can be found in difficult economical conditions of the majority of the population; low level of civil society; increasing individualization and income inequalities. The findings of this paper also demonstrate that the political and institutional structure is fairly unfavorable for local activists. The community organizations are not supported by the local governmental structures in a substantial way. On the contrary, they are faced, in most of the cases, with the authority’s alienation and confrontation.Keywords: community organizations, Vilnius, urban movements, post-Soviet city, urban policy, Lithuania.